STUDI KELENGKAPAN PENJELASAN CARA PENGGUNAAN SEDIAAN CONTROLLER INHALER (KOMBINASI KORTIKOSTEROID DENGAN BETA-2 AGONIS) JENIS DISKUS® DAN TURBUHALER® OLEH APOTEKER DI APOTEK - Amelia Lorensia; Doddy De Queljoe; Bella Lony Karina; Astri Heru (Jurnal Ilmiah Manuntung, 2016)
Asthma is a chronic disease that can be controlled by treatment with a controller containing a corticosteroid combination with beta-2 agonists, which are available in the form Diskus® and Turbuhaler® which is DPI (dry powder inhaler) in Indonesia. Techniques improper use can give less than optimal results, therefore, the role of pharmacists to provide education in the form of how to explain the inhaler. This study aims to find out information on how to use Diskus® and Turbuhaler® by pharmacists to patients with asthma in the pharmacy area of the city of Surabaya. This research is non-experimental research with cross sectional method, and using observation techniques in the form of a checklist. Sampling by non-random sampling method by using purposive. The data will be processed with descriptive statistical analysis. Based on the results of research on the use of information studies preparation Diskus® explanation is given, it can be concluded there is no pharmacist in the category optimal technique that is able to mention all the steps properly. Most pharmacists categorized adequate technique for the pharmacist is able to name all of the critical step. While on how to use Turbuhaler® information provided by pharmacists in explaining Turbuhaler to patients in pharmacies is still lacking for by an explanation of each step are not all pharmacists can explain all the steps correctly and based on the critical step yet pharmacists who achieve adequate and optimal techniques.